Design And Analysis of Existing Storm Water Drainage Lines for Area Using Bentley’s Storm Cad: Design and analysis of storm water drainage network using Bentley's StormCAD (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Storm CAD is a comprehensive modeling software program for design and analysis of storm sewer system. StormCAD provides calculations for catchment runoff, inlet capacity and gutters pipe network flow. StormCAD can import and export drainage data directly from INROADS, StormCAD allows the input of external contributing areas, additional flow and carry over flow to model non-local runoff contributing to the discharge at any inlet. StomCAD provides several methods for computing travel time, including full pipe velocity, normal velocity, average end velocity and weighted average velocity. For the efficient functioning of the any housing or industrial sector proper drainage facilities is a must. To overcome these problems simulation of the existing network of the areas or zones is essential is carried out by using StormCAD. Effective management of storm water runoff is the basic necessity which will help in satisfying the above objectives. Absence of storm water management will result in pollution, sedimentation, local flooding, stream channel instability, declination in the level of ground water table etc. These effects can be reduced to some extent by having a well-designed drainage network. A properly designed storm drainage network will contribute in appropriate disposal of storm runoff, which will help in reducing the stagnant water bodies’ formation in the locality due to inappropriate execution of drainage network.